Stanisław Lubieniecki (1623-1675) jako uczestnik res publica litteraria - Jasiński, Maciej (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
Stanisław Lubieniecki (1623-1675), best known for his work as a historian and theologian of the Polish Brethren, published also the Theatrum cometicum (Amstelodami 1666-1668) devoted to cometary studies. The first volume of that book contains the author’s astronomical correspondence with dozens of more or less renowned scholars of various fields of knowledge. By initiating scientific correspondence, Lubieniecki attempted to act as an intermediary in conveying information in 17th century Res Publica Litteraria. The article explains this activity on the basis of several examples: the issue behind the total number of comets in 1664 and 1665, the phenomenon in the Andromeda Galaxy and Lubieniecki’s correspondence with Henry Oldenburg. It shows how a layman in the world of science seeks to find a place for himself in the republic of scholars.